Pengaruh Kepuasan Kerja Dan Stress Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan PT Tandoox Global Indonesia) - Siti Rahma Oktaviola; Herudini Subariyanti (Politeknik Kampar, 2023)
Performance is the implementation of a pre-planned strategy. The implementation of performance is carried out by human resources who possess abilities, competencies, motivation, and interests. This study aims to analyze the influence of job satisfaction and work stress on employee performance. The research method used is quantitative descriptive with primary data collection through distributing questionnaires to 53 employee respondents. The data analysis techniques used in this study include descriptive analysis, instrument data testing including validity and reliability tests, classical assumption tests including tests of normality, multicollinearity, heteroscedasticity, and autocorrelation, multiple linear regression analysis, and hypothesis testing including t-test, F-test, and coefficient of determination test. The results of this study indicate that the independent variable, job satisfaction, has a positive influence on employee performance, with a resulting significance value of 0.000 < 0.05. This means that job satisfaction significantly affects employee performance. On the other hand, work stress has a negative influence on employee performance, with a resulting significance value of 0.000 < 0.05. This indicates that work stress significantly impacts employee performance. The results also show an adjusted R-squared value of 65%, which means that the influence of job satisfaction and work stress on employee performance is categorized as moderate.